The computer in secondary school mathematics : an analysis and classification of possible modes of application, with suggested implications for the mathematics curriculum in South Africa - Marsh, Terence Anthony (Rhodes University, Faculty of Education, Department of Education, 1991)
There is a variety of possible ways in which computers can be used to enhance mathematics education. This thesis attempts to identify, analyse and classify these possibilities, particularly at the secondary school level. It describes and exemplifies applications ranging from drill-and-practice through games and simulations to problem solving by computer programming. Software evaluation procedures are considered in some depth. Illuminative evaluations of various items of software and there classroom use are reported. The underlying methodology is small-scale action research. Insights gained during the process of investigating each class of software lead to the eventual formulation of a scheme for classifying mathematics education software by means of 'multidimensional attributes'. It is contended that this scheme will help mathematics teachers to make well informed and sound professional judgements regarding the evaluation and use of computer programs for teaching/learning purposes. Also, it is hoped that this scheme and the thesis as a whole will contribute towards the establishment of well founded standards and procedures for software development in the field of mathematics education. Several implications of the computer for the mathematics curriculum in South Africa are suggested. A note of caution is sounded regarding possible detrimental effects of the computer and several questions requiring further research are posed. A recommendation arising from the thesis is that in-service training courses concerning computer applications in mathematics education should be run for secondary school teachers.
Keywords: Mathematics -- Computer-assisted instruction; Mathematics -- Study and teaching (Secondary) -- South Africa